Beta angle in a sample of Iraqi adults with Class I skeletal and dental relations and its correlation with other craniofacial measurements - Mohammed Nahidh; Sara M J Al-Mashhadany (College of Dentistry/ University of Baghdad, 2013)
Background: This study aimed to determine the value of Beta angle for a sample of Iraqi adults with class I skeletal and dental relations and to verify the existence of sexual dimorphism and to find out the relation between this angle and other craniofacial measurements. Materials and Methods: Sixty dental students (23 males and 37 females) with an age ranged between 20-31 years old and having class I skeletal and dental relations were chosen for this study. Each student was subjected to clinical examination and digital true lateral cephalometric radiograph. The radiographs were analyzed using AutoCAD 2007 computer program to measure the angular and linear variables. Descriptive statistics were obtained for the measurements for both genders and total sample; independent samples t-test was performed to evaluate the gender difference and Pearson's correlation coefficient test used to detect the relation between the Beta angle and other measurements. Results and Conclusions: The value of Beta angle in this study was 32.63 2.57. When the Beta angle is less than 27, the case is class II and when it is more than 38, the case is class III. There is no genders difference regarding the Beta angle and this angle correlated significantly and positively with the mandibular length and articular angle and negatively with ANB and saddle angles.